Caregiver Behavioral Conditioning Strategies in Orphanage Child Development: Strategi Pengkondisian Perilaku Pengasuh dalam Perkembangan Anak di Panti Asuhan - Musa Al Asad Ramadhan; Budi Haryanto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Child development requires structured education, supervision, and moral guidance, particularly for children living in orphanages who often experience social, emotional, and behavioral challenges due to disadvantaged family backgrounds. Specific Background Orphanages function not only as social welfare institutions but also as environments responsible for shaping behavior through organized caregiving systems and educational programs. The Putra Kediri Orphanage applies behavioristic principles, especially classical conditioning, to address negative behavioral patterns among foster children. Knowledge Gap Previous studies on orphanage care primarily discuss character education and religious guidance but rarely examine the integrated practical application of behavioristic theory within caregiving strategies. Aims This study aims to identify and analyze caregiver strategies used to transform children’s behavior through structured interventions grounded in classical conditioning theory. Results Using a case study approach with Miles, Huberman, and Saldana data analysis, findings reveal that behavior transformation is achieved through interconnected strategies including in-depth interviews, continuous supervision, environmental regulation, weekly evaluations, reward and punishment systems, counseling interventions, religious education, life-skills training, leadership programs, and social awareness activities, which collectively reduce negative behavior and support academic and personal development. Novelty The study demonstrates a comprehensive integration of classical conditioning principles into daily caregiving practices within an orphanage setting through coordinated behavioral management and developmental programs. Implications These findings provide a structured caregiving framework that can inform behavioral management models and institutional child development practices in social welfare institutions seeking systematic approaches to positive behavioral formation. Highlights: Integrated Supervision and Structured Evaluation Support Consistent Behavioral Transformation Among Foster Children. Combined Counseling, Religious Instruction, and Developmental Programs Foster Moral and Personal Growth. Controlled Residential Environments Help Maintain Stability and Reduce Recurrence of Maladaptive Conduct. Keywords: Classical Conditioning, Caregiver Strategies, Orphanage Care, Behavior Modification, Child Development